Physiological characterization in medicinal Cannabis plants during different phenological stages under biotic stress - Rodríguez-Yzquierd, Gustavo Adolfo (2021)
Introduction. Plants exposed to stress conditions, alter their functioning and generate physiological responses that affect their agronomic performance. In the cultivation of medicinal Cannabis, research on plant physiology and its interaction with biotic factors is scarce. Objective. To determine physiological variables indicative of stress in different phenological stages of Cannabis plants in greenhouse and under contrasting phytosanitary conditions. Materials and methods. The study was carried out between November and December 2019, in the municipality of Rionegro, Antioquia, Colombia. Batches of Cannabis sativa L. plants coming from asexual multiplication were sown weekly. Between weeks six and twelve after transplanting, the chlorophyll index and fluorescence variables (basal=Fo, maximum=Fm and variable=Fv), ambient crop thermal differential, water stress index, and foliar nutrient concentration were evaluated from the beginning of its vegetative phase to the reproductive and productive phase, under two contrasting phytosanitary conditions, one with white rot caused by Sclerotinia sclerotiorum and the other without pests or pathogens. Results. The plants did not present abiotic stress affecting the photosynthetic apparatus at any stage. The values of each nutrient were within the optimal ranges and the edaphic factors did not represent a limitation for the development of the crop. Reference values of physiological variables were defined at different phenological stages under optimal development conditions. In diseased plants with S. sclerotiorum, the chlorophyll index, water stress index, and fluorescence, showed reference values that can be useful for the identification of detrimental effects in the photosystem II. Conclusions. In diseased plants the chlorophyll index and the parameters Fv/Fm and Fv/F0 constituted indicator variables to detect biotic stress in Cannabis plants. In healthy plants, Fv/Fm, Fv/Fo, CWSI, and chlorophyll index can be evaluated in agronomic crop management experiments.